2010
DOI: 10.1007/s12665-010-0525-3
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of potential seismic hazard and site effect in Antakya (Hatay Province), SE Turkey

Abstract: Antakya city is at risk because of strong earthquakes occurring in the area, and different soil conditions that can produce variation of the ground motion amplification. Microzonation of cities provides a basis for site-specific hazard analysis in urban settlements. In particular, seismic microzonation can be provided by means of detailed seismic assessment of the area, including earthquake recordings and geological studies. In this paper, we propose a preliminary microzonation map for the city of Antakya, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 28 publications
(23 reference statements)
1
14
0
1
Order By: Relevance
“…It is essential to realize local soil conditions and seismicity characteristics of the region and make them usable in building design and evaluation. The obtained earthquake parameter values directly affect the calculations related to the structural analysis (Borcherdt, 2004;Över et al, 2011;Büyüksaraç et al, 2013;Karaşin and Işık, 2017;Işık et al, 2016aIşık et al, , 2016bIşık and Kutanis, 2015;Kutanis et al, 2018, Bekler et al, 2019.…”
Section: Earthquake -Building Parameters For Structural Analysesmentioning
confidence: 99%
“…It is essential to realize local soil conditions and seismicity characteristics of the region and make them usable in building design and evaluation. The obtained earthquake parameter values directly affect the calculations related to the structural analysis (Borcherdt, 2004;Över et al, 2011;Büyüksaraç et al, 2013;Karaşin and Işık, 2017;Işık et al, 2016aIşık et al, , 2016bIşık and Kutanis, 2015;Kutanis et al, 2018, Bekler et al, 2019.…”
Section: Earthquake -Building Parameters For Structural Analysesmentioning
confidence: 99%
“…It is therefore classified into the highest seismic zone of the current Turkish Seismic Code (TMPS 1998). Figure 2a indicates the main historic events and fault lines according to Över et al (2011) and Pawlewicz et al (2002), as well as the current seismicity indicated by earthquakes that occurred in the vicinity from 2006 until 2009. The historical earthquakes shown with epicenters in the close surroundings (approximately a 7 km distance) have caused heavy damage corresponding to intensities IX or X (Tan et al 2008).…”
Section: Site and Hazard Characterizationmentioning
confidence: 99%
“…Several scientists particularly studied on the tectonics of the study region (Yurur and Chorowicz 1998;Rojay et al 2001;Adiyaman and Chorowicz 2002;Yurtmen et al 2002;Over et al 2004;Tatar et al 2004;Westaway 2004;Akyuz et al 2006;Korkmaz 2009Korkmaz , 2010Over et al 2011). Yurur and Chorowicz 1998;Rojay et al 2001;Adiyaman and Chorowicz 2002;Yurtmen et al 2002;Over et al 2004;Tatar et al 2004;Westaway 2004;Akyuz et al 2006;Over et al 2011 informed that there is a significant fault zone, the Karasu Fault Zone (KFZ), which bounds the western margin of the KVZ in the Hatay province, takes up a part of the left-lateral slip between the African and The SRTM acquires elevation data on a near-global scale to generate the most complete medium-resolution digital topographic database of the earth.…”
Section: Study Areamentioning
confidence: 99%
“…Yurur and Chorowicz 1998;Rojay et al 2001;Adiyaman and Chorowicz 2002;Yurtmen et al 2002;Over et al 2004;Tatar et al 2004;Westaway 2004;Akyuz et al 2006;Over et al 2011 informed that there is a significant fault zone, the Karasu Fault Zone (KFZ), which bounds the western margin of the KVZ in the Hatay province, takes up a part of the left-lateral slip between the African and The SRTM acquires elevation data on a near-global scale to generate the most complete medium-resolution digital topographic database of the earth. The SRTM consisted of a specially modified radar system that flew onboard the Space Shuttle Endeavor (The Global Land Cover Facility, http://glcfapp.umiacs.umd.edu:8080/esdi/ index.jsp).…”
Section: Study Areamentioning
confidence: 99%